2022
DOI: 10.3389/fmolb.2022.1012505
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis regulator SLC7A11 is a prognostic marker and correlated with PD-L1 and immune cell infiltration in liver hepatocellular carcinoma

Abstract: Background: Liver hepatocellular carcinoma (LIHC) is a complicated disease with poor survival and lack of viable treatment options. The roles of ferroptosis and immunotherapy in LIHC are increasingly prominent, but the interplay of ferroptosis with the tumor microenvironment (TME) in LIHC is currently under-investigated.Methods: In this study, we analyzed normal liver tissues and tumor tissues from the TCGA and GTEx databases to obtain differentially expressed ferroptosis-related genes (FRGs). We then clustere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Increasing evidence indicates that SLC7A11 is a ferroptosis suppressor gene that is overexpressed in many human cancers 25 . In addition, it is a member of the cystine/glutamate antiporter protein, which is used to uptake cysteine for glutathione biosynthesis and anti-aging agent defense 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence indicates that SLC7A11 is a ferroptosis suppressor gene that is overexpressed in many human cancers 25 . In addition, it is a member of the cystine/glutamate antiporter protein, which is used to uptake cysteine for glutathione biosynthesis and anti-aging agent defense 26 .…”
Section: Resultsmentioning
confidence: 99%
“…4 B). Notably, accumulating studies have indicated SLC7A11 as a ferroptosis suppressive gene that may be overexpressed in many human cancers [ 25 ]. SLC7A11 (also known as xCT) is a member of the constituent cystine/glutamate reverse transporter proteins for uptake of cysteine for glutathione biosynthesis and antioxidant defense [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glutaminolysis generates fuel to maintain the primary energy electron transport chain (ETC) and provide carbon to support redox homeostasis, and also produces citrate to safeguard lipid biosynthesis processes. 17 Gln plays an important role both in the process of viral infection and in the antiviral process of immune cells ( Figure 1 ).
Figure 1 The biological process of glutamine metabolism in CD4 + T cells.
…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“… 13 Positive correlation between SLC7A11 expression and TFH cells in liver hepatocellular carcinoma with poor survival. 17 However, glutaminolysis is utilised differently by TFH cells in the older adults. Sustained activation of the mechanistic target of mammalian target of rapamycin 1 (mTORC1), which depends on SLC7A5 as an amino acid source, leads to loss of cell differentiation, such as TFH and memory precursor cells, in the CD4 + T cell response of older adults.…”
Section: Glutaminolysis Determines Cytokine Signalling and T Helper C...mentioning
confidence: 99%